ประวัติศาสตร์บริเวณชลบุรีก่อนสมัยอยุธยา - จำปาพันธ์ กำพล (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2016)
บทความนี้นำเสนอผลการศึกษาเกี่ยวกับแหล่งชุมชนโบราณย่านลุ่มแม่น้ำพานทอง และชายฝั่งทะเลตะวันออกในเขตจังหวัดชลบุรี ด้วยวิธีการที่เรียกว่า “ประวัติศาสตร์บริเวณ” พบว่า ชลบุรีเป็นที่ตั้งของเมืองโบราณที่มีพัฒนาการมาตั้งแต่สมัยทวารวดี เขมรพระนคร และอโยธยา อาทิเช่น “เมืองพระรถ”ตั้งอยู่ที่ตำบลหน้าพระธาตุ อำเภอพนัสนิคม, “เมืองศรีพโล” ตั้งอยู่ที่ตำบลเขาบางทราย อำเภอเมืองชลบุรี,“เมืองพญาเร่” ตั้งอยู่ที่บ่อทอง อำเภอบ่อทอง เป็นต้น โดยใช้วิธีการศึกษาเชิงสำรวจสภาพทางภูมิศาสตร์ของสถานที่ตั้งเมือง การตรวจสอบอายุของหลักฐานประเภทโบราณคดี เพื่ออธิบายถึงสภาพของบ้านเมืองในย่านชายฝั่งทะเลตะวันออกของชลบุรี ก่อนการเข้าสู่การเป็นส่วนหนึ่งของราชอาณาจักรสยาม ที่มีกรุงศรีอยุธยาและลุ่มแม่น้ำเจ้าพระยาเป็นศูนย์กลางทางวัฒนธรรมในภูมิภาค This article is presenting the study result of the ancient sites in the Panthong riverbasin and the eastern coast of Chonburi province by using the methodology called the“Total History”. It was found that Chonburi was and ancient city built in many periodssuch as Dvaravati, Angkor of Khmer kingdom, and Ayothaya in Chaophraya river basin. The“Phrarot city” in Naphratat Sub-district of Phanatnikhom District in Chonburi province andthe “Siphalo city” in Khaobangsai Sub-district of Chonburi city district and the “Phayarecity” in Bothong Sub-district of Bothong District in Chonburi province etc.The field studiesabout that geographies of cities and the dating of the archaeologies evidences were usedto explain about the condition of the city before being a part of Siamese Kingdom. Inwhich Ayutthaya and the Chaopraya river basin was the cultural center in this region.